2010
DOI: 10.4102/aveh.v69i2.129
|View full text |Cite
|
Sign up to set email alerts
|

Refractive error in school children in Agona Swedru, Ghana

Abstract: Uncorrected refractive errors remains a public health problem among different population groups. Among schoolchildren, uncorrected refractive errors have a considerable impact on learning andacademic achievement especially in underserved and under-resourced communities. A school based cross-sectional study was carriedout to estimate the prevalence and distribution of refractive error among schoolchildren in the Agona Swedru municipality of Central Region of Ghana. 637 schoolchildren aged 11-18 years old were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
51
5
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 10 publications
8
51
5
1
Order By: Relevance
“…The proportion of children who had previously had an eye examination in this study (0.6%) is comparable to 0.58% reported for rural India 6 but slightly more than the 0.3% reported for school children in Agona District of the Central Region of Ghana 21 . It is considerably less than 30.3% among students in Tanzania, 22 , 42.3% in Egypt 15 , and 2.7% in South Africa.…”
Section: Discussionsupporting
confidence: 70%
“…The proportion of children who had previously had an eye examination in this study (0.6%) is comparable to 0.58% reported for rural India 6 but slightly more than the 0.3% reported for school children in Agona District of the Central Region of Ghana 21 . It is considerably less than 30.3% among students in Tanzania, 22 , 42.3% in Egypt 15 , and 2.7% in South Africa.…”
Section: Discussionsupporting
confidence: 70%
“…But the fogging technique as used herein has been reported in previous studies. 16 The results of this study showed that 32.1% of the children examined had eye problems, this finding being higher than the results in other studies within Nigeria. In Anambra, a 6.1% prevalence in eye diseases was found among school children, 10 whereas in a similar study carried out in the northern part of Nigeria, 22.6% was reported as the prevalence of ocular disorder among children who participated in the school eye screening.…”
Section: Discussioncontrasting
confidence: 66%
“…In a study in Debark and Kola Diba towns, northern Ethiopia, the prevalence of visual impairment due to refractive errors in schoolchildren was 7.6 per cent . In Ghana, visual impairment (VA of 6/12 or worse in the better eye) was present in 4.5 per cent of the children examined . In a study conducted in India, 5.1 per cent of children in schools had VA of worse than 6/12 in the better eye .…”
mentioning
confidence: 91%